Effect Of Water Absorption Towards Mechanical And Physical Properties Of Hybrid Flax/Glass Fiber Laminated Composites - Mohd Jaffri, Ju Liyana (Universiti Sains Malaysia, 2022)
The moisture uptake of flax/glass hybrid laminated composite in the function of time after immersion in various solutions was studied. Synthetic fiber and natural fiber were combined by using hybrid concept. Two type nine layers of hybrid composites with different stacking sequences were fabricated using both hand lay-up and vacuum bagging technique. The laminates were subjected to water absorption which were immersed into various solutions of different pH level for 21 days. The characterization involving mechanical testing of tensile test, flexural test and impact test and morphological analysis by using scanning electron microscope (SEM). Degradation was expected after ageing in the different solutions in which the water molecules break down the structure in the composites. It was found that composite immersed in basic solution can deteriorate faster than in distilled water and acidic solution. The outcome of mechanical testing results in almost similar trend which the mechanical properties of immersed samples decreased with increasing immersion time indicating fiber degradation. The morphological analysis obtained from fracture surface of tensile and impact test and showed that all samples have defect especially voids and poor interfacial adhesion due to the composites were prepared were inconsistent. It was also found that hybrid composites with more glass fiber layers have higher mechanical properties compared to FF/GF composite.